Longitudinal alterations of pulmonary V.O2 on-kinetics during moderate-intensity exercise in competitive youth cyclists are related to alterations in the balance between microvascular O2 distribution and muscular O2 utilization - Hovorka, M.; Prinz, B.; Simon, D.; Zöger, M.; Rumpl, C.; Nimmerichter, A. (Frontiers in Sports and Active Living, 2022)
Purpose: The main purpose of the current study was to investigate the dynamic adjustment of pulmonary oxygen uptake (V.O2) in response to moderate-intensity cycling on three occasions within 15 months in competitive youth cyclists. Furthermore, the muscle ?deoxy[heme] on-kinetics and the ?deoxy[heme]-to-V.O2 ratio were modeled to examine possible mechanistic basis regulating pulmonary V.O2 on-kinetics.